STUDY PROTOCOL – pulsed radiofrequency in addition to transforaminal epidural steroid injection in patients with acute and subacute sciatica due to lumbosacral disc herniation: rationale and design of a phase III, multicenter, randomized, controlled trial. (1st September 2020) - Scipione, Roberto; Alfieri, Giulia; De Maio, Alessandro; Panella, Emanuela; Napoli, Simone; Bianchi, Luca; Pandaloro, Nunziante; Bazzocchi, Alberto; Facchini, Giancarlo; Albisinni, Ugo; Spinnato, Paolo; Catalano, Carlo; et al.
ABSTRACT: Lumbosacral disc herniation (LDH) represents the most common cause of sciatica. Currently, there is limited evidence about minimally invasive interventional therapies for the treatment of this condition. This paper presents the protocol for a multicenter, prospective, randomized, controlled, phase III trial evaluating if PRF in addition to TFESI leads to better outcomes in patients with sciatica due to LDH, compared to TFESI alone, during the first year after treatment (Pulsed Radiofrequency in Addition to TFESI for Sciatica [PRATS]). Eligible patients are between 18 and 75 years of age, suffer from sciatica of less than 12-week duration with pain intensity >4 on the Visual Analogue Scale (VAS) and have unilateral LDH compatible with symptoms at MRI. The Medical Ethics Committee of participating hospitals approved the study protocol. Patients will be randomized to receive either combined treatment (PRF and TFESI) or TFESI alone. The primary outcome will be the assessment of pain intensity with VAS at different timepoints from week-1 to 52 after treatment; secondary outcomes will include Roland Disability Questionnaire for sciatica and Oswestry Disability Index, evaluated at 4, 12 and 52 weeks. The follow-up will last 52 weeks for each patient. Statistical analysis will be performed on a per-protocol basis.